Tuning Catalytic Properties of Supported Bimetallic Pd/Ir Systems in the Hydrogenation of Cinnamaldehyde by Using the “Water-in-Oil” Microemulsion Method - Tomasz Szumełda; Alicja Drelinkiewicz; Francesco Mauriello; Maria Grazia Musolino; Anna Dziedzicka; Dorota Duraczyńska; Jacek Gurgul (Journal of Chemistry)
Supported Pd/Ir bimetallic catalysts were synthesized by the “water-in-oil” microemulsion method at different precursor concentrations and characterized by XRD, XPS, SEM, TEM, and cyclic voltammetry. Depending on the preparation conditions, formation of bimetallic catalysts with different metal segregation and surface composition can be easily obtained, thus tuning the bimetallic structure of catalysts as well as their relative catalytic properties. Bimetallic Pd/Ir systems were efficiently tested in the hydrogenation of cinnamaldehyde showing a better performance than analogous monometallic catalysts.